Female Labor Force Participation in Pakistan: Assessing the Barriers and Exploring the Legal Mechanisms - khalid, ifrah (Journal of Public Policy Practitioners, 2025)
The female labor force participation in Pakistan has been significantly low even though women in the country are almost half the national population. This happens despite the formal promises regarding gender equality and inclusive development. This systematic disparity can be explained by the strongly embedded socio-cultural beliefs and structural circumstances that restrict access to paid labour and economic mobility systematically among women. The main objective of the study is to investigate both the socio-cultural and structural obstacles regarding the low rate of participation of the female labor force in Pakistan, and to understand the effectiveness of the current policy enactment mechanisms (legal and workplace) aimed at making labour market assessible for women. To conduct a qualitative study, the research design based on secondary data analysis was considered, and national statistics, international reports, legal tools, and policy documents were used. Thematic analysis was used to extract common themes that define the outcomes of women in the labor market. The results note that patriarchal culture and restrictions in movement, security at their places of work, wage disparities, and poor implementation of the laws all weaken the engagement of women. The research suggests the adoption of the implementation mechanisms to achieve safer and more inclusive workplaces.